Sodium Valproate is More Effective than Pizotifen in the Prophylaxis of Migraine Patients (Bangladesh Journal of Neuroscience, 2013)
Background and objectives: Migraine is now ranked as number 19 among all diseases causing disability by WHO1 which is characterized by recurrent attacks of various combinations of headache and neurological, gastrointestinal and autonomic symptoms2 accompanied by photophobia, phonophobia and vomiting3. The treatment of migraine involves acute, preventive drugs and non-pharmacological strategies. The basic principle in management of migraine is avoiding the trigger factors, blocking the mediators and splinting the end organ4. Though there is no significant curable treatment but there are some internationally proven and well accepted prophylactic medication which reduces headache severity, frequency, duration and risk for rebound5. Sodium valproate and pizotifen are commonest of them6, where sodium valproate is more effective than pizotifen in the prophylaxis of migraine patients. Methods: This study was a single blind randomized clinical trial carried out in the neurology outpatient department of Bangabandhu Sheikh Mujib Medical University, Dhaka (BSMMU) for the period of 2 years, among adult patients between the age of 16-50 years. Results: A total of 120 patients were included & divided into two groups such as group-A(60 patients) treated by sodium valproate & group-B(60 patients) treated by pizotifen for a period of 6 months and followed up every two months for 3 times and showed sodium valproate is more effective than pizotifen. Conclusion: This study permit to conclude that efficacy of sodium valproate is more than pizotifen in the prophylaxis of migraine patients. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17174 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 81-87